Improving Students' Communication Skills and Understanding of Equivalent Fractions Through Project Based Learning With Toast Maker - Ambawono, Gancar Pramistri; Rahayuningsih, Setiti Rahayuningsih; Siti Inganah (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This study aims to explore the effectiveness of the Project-Based Learning (PjBL) model in improving students' understanding of equivalent fractions and their communication skills at SD Muhammadiyah 4 Malang. Through the "Toast Maker" project, fourth-grade students were involved in practical activities that allowed them to apply the concept of equivalent fractions in real contexts. The research method used was quantitative with an experimental design, involving 26 students who were divided into two groups: an experimental group that implemented PjBL and a control group that used conventional learning methods. Data were collected through pre-tests and post-tests to measure improvements in students' understanding, as well as presentation assessments to evaluate communication skills. The results showed that the average score of students' understanding increased from 55 in the pre-test to 80 in the post-test, with the percentage of learning completion increasing from 38% to 92%. In addition, the average group presentation score reached 85, indicating that students were able to convey their project results well. Qualitative feedback from students also showed increased engagement and motivation during the learning process. This study concludes that the implementation of the PjBL model is not only effective in improving students' academic understanding but also contributes to the development of social and communication skills that are important for their personal development.